Isoflurane Modulates Hippocampal Cornu Ammonis Pyramidal Neuron Excitability by Inhibition of Both Transient and Persistent Sodium Currents in Mice. (July 2019) - Zhao, Wenling; Zhang, Mingyue; Liu, Jin; Liang, Peng; Wang, Rurong; Hemmings, Hugh C.; Zhou, Cheng
Editor's Perspective: What We Already Know about This Topic: Neurotransmitter release from presynaptic nerve terminals is hindered by volatile anesthetics through inhibition of voltage-gated sodium channels Depression of neuronal activity by volatile anesthetics through direct inhibition of sodium currents in excitatory neurons has not been previously reported What This Article Tells Us That Is New: Electrophysiologic studies show that isoflurane, at clinically relevant concentrations, inhibits both transient and persistent sodium currents on mouse cornu ammonis hippocampal neurons ex vivo The isoflurane-induced inhibition of sodium channels on excitatory neurons may contribute to the reduction of neuronal excitability and synaptic transmission Background: Volatile anesthetics inhibit presynaptic voltage-gated sodium channels to reduce neurotransmitter release, but their effects on excitatory neuron excitability by sodium current inhibition are unclear. The authors hypothesized that inhibition of transient and persistent neuronal sodium currents by the volatile anesthetic isoflurane contributes to reduced hippocampal pyramidal neuron excitability. Methods: Whole-cell patch-clamp recordings of sodium currents of hippocampal cornu ammonis pyramidal neurons were performed in acute mouse brain slices. The actions of isoflurane on both transient and persistent sodium currents were analyzed at clinically relevant concentrations of isoflurane. Results: The median inhibitory concentration of isoflurane for inhibition of transient sodium currents was 1.0 ± 0.3 mM (~3.7 minimum alveolar concentration [MAC]) from a physiologic holding potential of −70 mV. Currents from a hyperpolarized holding potential of −120 mV were minimally inhibited (median inhibitory concentration = 3.6 ± 0.7 mM, ~13.3 MAC). Isoflurane (0.55 mM; ~2 MAC) shifted the voltage-dependence of steady-state inactivation by −6.5 ± 1.0 mV (n = 11, P < 0.0001), but did not affect the voltage-dependence of activation. Isoflurane increased the time constant for sodium channel recovery from 7.5 ± 0.6 to 12.7 ± 1.3 ms (n = 13, P < 0.001). Isoflurane also reduced persistent sodium current density (median inhibitory concentration = 0.4 ± 0.1 mM, ~1.5 MAC) and resurgent currents. Isoflurane (0.55 mM; ~2 MAC) reduced action potential amplitude, and hyperpolarized resting membrane potential from −54.6 ± 2.3 to −58.7 ± 2.1 mV (n = 16, P = 0.001). Conclusions: Isoflurane at clinically relevant concentrations inhibits both transient and persistent sodium currents in hippocampal cornu ammonis pyramidal neurons. These mechanisms may contribute to reductions in both hippocampal neuron excitability and synaptic neurotransmission. Abstract : Electrophysiologic studies show that isoflurane, at clinically relevant concentrations, inhibits both transient and persistent sodium currents on mouse cornu ammonis hippocampal neurons ex vivo . The isoflurane-induced inhibition of sodium channels on excitatory neurons may contribute to the reduction of neuronal excitability and synaptic transmission.